How Sociocultural Factors Influence Patient Satisfaction And Complaint Management In Hospitals (The Review of Diabetic Studies, 2025)
Patient satisfaction has emerged as a cornerstone of quality assessment in modern healthcare, serving as a critical indicator that influences clinical outcomes, patient loyalty, and even the frequency of medical malpractice claims [1]. It is widely regarded as an effective, albeit indirect, measure of the overall success of physicians and hospital systems [2]. This evolution in perspective is part of a broader paradigm shift within the healthcare industry toward a model of consumerism, where patients are increasingly viewed as "consumers of healthcare". This shift is propelled by rising patient expectations for transparency and immediate access to services, carrying significant financial implications; the loss of a single dissatisfied patient can result in the forfeiture of over $200,000 in potential income over the lifetime of a practice [3].